Speaking valve with integrated biomimetic overpressure release and acoustic warning signal - N. Knorr; P. Auth; S. Kruppert; C. A. Stahl; K. M. Lücking; F. Tauber; T. Speck (Scientific Reports)
Abstract Speaking valves enable tracheostomy patients to speak naturally. However, improper use may cause dangerous overpressure, leading to severe complications or even patient’s death. We address this life-threatening issue by creating a biomimetic speaking valve, which incorporates an integrated overpressure valve that automatically opens when reaching critical pressure levels. To enhance safety, we integrated a whistle module to provide an audible alert for medical staff. Fundamental research on the Utricularia vulgaris trapdoor inspired our abstracted valve form. Through a comprehensive analysis using generalized linear mixed-effect models, we examined various membrane parameter effects on the function of the biomimetic overpressure valve. This enabled us to adjust the valve’s opening pressure to cater to patient’s unique requirements, thus potentially saving lives by applying a solution from nature.